Separation of Cu, Sn, Pb from copper scrap coated with Sn and Pb - Yoo, Kyoungkeun; Moon, G. (2015)
Tin/lead plating technologies have been used for unsurpassed solderability and in electrical and electronic equipments eliminating the potential for tin whisker formation. The present study is aimed at recovering of Cu, Sn, Pb, respectively, from the copper scrap coated with Pb and Sn. In the recycling process, tin was selectively leached from the scrap, and lead precipitated into PbCl2 powder. Because copper was not dissolved, so tin, lead, copper were recovered, respectively. The leaching tests were performed to investigate the effects of leaching conditions such as temperature, agitation speed, and oxidant concentration. In the process, the oxidant could be reused by electrical oxidation.